FROM SPORTS ACTIVITIES TO SPORTS SERVICE - Šemsudin Džeko; Spasoje Bjelica (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
From sports activities to sports service, development and actualization of sport goes through particular forms of organization. Those are sports events, sports divisions, individual departments, types of sports and similar. This paper attempts to indicate the connection and correlation of the mentioned elements in the frame of an overall sport activity organization.